Evaluation pre-service teacher numeracy – build bridges rather than roadblocks - Cooke, Audrey (Uni Print, 2015)
Numeracy is an important skill for many university students. In particular, it is being focused upon for pre-service teachers through the development and administration of skills tests that address numeracy and literacy. These tests are high-stakes as they have the capacity to stop pre-service teachers from completing their qualifications or registering with the required teaching authority. The aim of this theoretical research report is to explore the potential impacts of a high-stakes numeracy test and to discuss whether these impacts have unexpected consequences for pre-service teachers, pre-service teacher educators, and the community.